Analysisi wk6 PDF
Analysisi wk6 PDF
Analysisi wk6 PDF
Remark. In fact Cauchy’s insight would let us construct R out of Q if we had time.
9.2 Definition
Let (an ) be a sequence [R or C]. We say that (an ) is a Cauchy sequence if, for all ε > 0
there exists N ∈ N such that
Proof. 1 > 0 so there exists N such that m, n > N =⇒ |am − an | < 1. So for m > N ,
|am | 6 1 + |aN | by the ∆ law. So for all m
Proof. Let an → l and let ε > 0. Then there exists N such that
So
|am − an | 6 |am − l| + |an − l| by the ∆ law
< ε/2 + ε/2 =ε
1
9.5 Cauchy =⇒ Convergent [R]
Theorem. Every real Cauchy sequence is convergent.
Proof. Let the sequence be (an ). By the above, (an ) is bounded. By Bolzano-Weierstrass
(an ) has a convergent subsequence (ank ) → l, say. So let ε > 0. Then
m, n > N =⇒ |am − an |
6 |am − ans | + |ans − l|
< ε/2 + ε/2 =ε
Proof. Put zn = x + iy. Then xn is Cauchy: |xx − xm | 6 |zn − zm | (as |<w| 6 |w|). So
xn → x, yn → y and so zn → x + iy.
9.7 Example
Let
1 1 (−1)n+1
an = 1 −+ + ··· +
2 3 n
Then with m > n, and m − n odd we have
z }| {z }| { z }| {
1 1 1 1 1 1
|am − an | = − + − +...+ −
n + 1 n + 2 n + 3 n + 4 m − 1 m
1 1 1 1 1 1
= − + −...− + −
n + 1
| {z } | n + 2{z n + 3
} | m − 2{z m − 1 m
} |{z}
1 1
6 n+1 6 n
If m − n is even, we write
1 1 2
|am − an | = |am − am−1 + am | 6 |am − am−1 | + |am | 6 + 6
N +1 m n
1
Let ε > 0. Chose N > 2ε and convergence follows.
Question: What is limn→∞ an ? Later we’ll see it is log 2.
2
10 Series
10.1 Definition
Note. So far we have always used sequences defined by functions a : N → R. It is convenient
from now on to start off at a0 , that is to work with functions a : N ∪ {0} → R.
Pm
So let (an )∞ n=0 be a sequence of real (complex) numbers. Define sm := n=0 an , a well
defined real (complex) number.
Consider the P sequence (sn )∞ n=0 . We call this the series defined by the sequence (an ), and we
∞
denote it by n=0 an .
Note. This is a very odd name indeed! Don’t let it mislead you: ∞
P
n=0 an is just the sequence
a0 , a0 + a1 , a0 + a1 + a2 , . . . .
10.2 Examples
(1, 1 + x, 1 + x + x2 , . . . , 1 + x + x2 + · · · + xn , . . . )
1 P 1
(ii) The Harmonic Series Let an := n+1 . Then n+1 is
1 1 1
1, 1 + , 1 + + , . . .
2 2 3
x2
1, 1 + x, 1 + x, 1 + x + , . . .
2!
3
10.4 More examples
(i) Let an = xn .
xn is divergent.
P
(a) If x = 1 then
Proof. s0 = 1, s1 = 2, . . . , sn = n + 1 by induction.
1−xn+1
(b) If x 6= 1, then sn = 1−x .
1 1
Proof. s2n −1 = 1 + 2 + ··· + 2n =
1 1 1 1 1 1 1
= 1 + 2 + 3 + 4 + 5 + 6 + 7 + 8 + ...
1 2 4 2n−1
> 1 + 2 + 4 + 8 + ... + 2n
n
> 2
1 P 1
(iii) Let an = (n+1)2
. Then n2
is convergent.
Proof.
1 1 1 1
sn = 1 + 4 + 9 + ... + n2
+ (n+1)2
1 1 1
6 1 + 1·2 + 2·3 + ... +
n(n+1)
1 1 1 1 1 1
= 1 + 1 − 2 + 2 − 3 + ... + n − n+1
1
= 2− n+1
6 2
1
So (sn ) is monotone increasing [sn+1 = sn + (n+1)2
> sn ] and bounded by 2. So (sn ) is
convergent by Bolzano-Weierstrass (??).
4
10.5 Notation and its abuse
P∞ P∞
More notation: if the series n=0 an is convergent then we often denote the limit by n=0 an ,
and call it the sum.
Note. We must take great care, but Pthis double use is traditional.
P I will try to distinguish
the two uses, and say “The series an ” and “The sum an ”. I suggest that you do the
same for a bit.
10.6 Tails
Let (an ) be a sequence and (sn ) be the corresponding series.
Sometimes we want to look at (ak , ak+1 , ak+2 , . . . ). We write this series ∞
P
n=k an . We put
Sn = ak + ak+1 + · · · + an and note that what we said about Tails of sequences, and adding
constants, ensures that (sn ) is convergent if and only if Sn is convergent.
5
So l l
X X l X
l > k > N =⇒ an 6 |an | = |an | < ε
| k {z k } k
By the ∆ law
Note. Why is absolute convergence a good thing to have? Because it makes use of Cauchy
criterion easy!
10.10 Examples
10.11 Re-arrangements
P
Let p : N −→ N one-to-one and onto. WePcan then put bn = ap(n) and consider bn , which
we call a rearrangement of the series an .
Funny this can happen! Later on we will be able to prove that
Example.
1 1 1
1− 2 + 3 − 4 + ... → log 2
1 1 1
1+ 3 + 5 − 2 + 17 + 1
9 + 1
11 − 1
4 + ... → log(2/3)
P
Theorem. If (an ) is absolutely convergent and (bn ) is a rearrangement of (an ) then bn is
absolutely convergent too.
Then
P
(i) cn is absolutely convergent
P P P
(ii) cn = an bn
Proof.
6
(i) By pure algebra
N
X N
X 2
X 2N
X 2N
X
|an | |bn | 6 N |cr | 6 |an | |bn |
0 0 0 0 0
P P P
So by Sandwich Rule, |cn | is convergent to |an | |bn |.
P
(ii) Hence cn is convergent.
Note. Draw a diagram in the (r, s) plane marking out which ar bs are included in the various
sums.
Proof. an := xn , bn := xn , therefore
X
cn = xr xs = (n + 1)xn
r+s=n
(ii)
X xn X y n X (x + y)n
=
n! n! n!
xn yn
Proof. an := n! , bn := n! therefore
X xr y s (x + y)n
cn = =
r+s=n
r! s! n!